2022
DOI: 10.1021/acs.chemmater.1c04132
|View full text |Cite
|
Sign up to set email alerts
|

From Operando Raman Mechanochemistry to “NMR Crystallography”: Understanding the Structures and Interconversion of Zn-Terephthalate Networks Using Selective 17O-Labeling

Abstract: The description of the formation, structure, and reactivity of coordination networks and metal−organic frameworks (MOFs) remains a real challenge in a number of cases. This is notably true for compounds composed of Zn 2+ ions and terephthalate ligands (benzene-1,4-dicarboxylate, BDC) because of the difficulties in isolating them as pure phases and/or because of the presence of structural defects. Here, using mechanochemistry in combination with operando Raman spectroscopy, the observation of the formation of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 109 publications
0
19
0
Order By: Relevance
“…For each composition, all of the signals characteristic of the CA and CMC were detected as expected. The signals centered at approximately 170–180 ppm are of particular interest as they correspond to the carboxylic/ate groups and thus are a priori sensitive to the formation of coordination bonds . As a matter of fact, for all electrodes, a broad and unresolved signal centered at 180 ppm was detected which showed variations in peak maximum position and line width depending on the binder composition.…”
Section: Resultsmentioning
confidence: 97%
“…For each composition, all of the signals characteristic of the CA and CMC were detected as expected. The signals centered at approximately 170–180 ppm are of particular interest as they correspond to the carboxylic/ate groups and thus are a priori sensitive to the formation of coordination bonds . As a matter of fact, for all electrodes, a broad and unresolved signal centered at 180 ppm was detected which showed variations in peak maximum position and line width depending on the binder composition.…”
Section: Resultsmentioning
confidence: 97%
“…5 Subsequently, Leroy et al demonstrated that 17 O ssNMR analyses could provide valuable insight into the structure of Zn-terephthalate phases, isolated in pure form using ball-milling and operando analyses of the reaction medium. 6 Lastly, in a recent investigation by Goldberga et al , it was shown that the water molecules within calcium oxalate hydrates could be enriched in 17 O, further enabling to investigate the dynamics of the water molecules within these crystalline phases. 7 Moreover, the isotopic labelling of the water molecules in 2 H and 18 O was also performed as part of the same work.…”
Section: Introductionmentioning
confidence: 99%
“…11 While most ball-milling reactions are performed in absence of external heating, the movements of the beads are accompanied by impacts and frictional forces, which cause an increase in temperature within the reactor. 12,13 The extent of heat generated depends on both the milling conditions and the reagents involved. 12,14,15 For example, a temperature rise of ≈7-10 °C has been measured during the simple ball-milling of pure quartz or terephthalic acid for 15 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 The extent of heat generated depends on both the milling conditions and the reagents involved. 12,14,15 For example, a temperature rise of ≈7-10 °C has been measured during the simple ball-milling of pure quartz or terephthalic acid for 15 minutes. 12,14 Such an increase in temperature, in conjunction with the highly efficient mixing of the reagents, has been shown to be beneficial to help overcome the activation energy for some chemical reactions, and/or help accelerate their kinetics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation